2017
DOI: 10.1002/mus.25617
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐frequency ultrasound of fascicles in the median nerve at the wrist

Abstract: Fascicles within the median nerve at the wrist can be readily imaged. Ultrahigh-frequency ultrasound technology may be informative in a variety of disorders affecting the peripheral nervous system. Muscle Nerve 56: 819-822, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 8 publications
3
52
1
1
Order By: Relevance
“…In agreement with their findings, the present study has demonstrated the feasibility of UHF ultrasound for visualizing single nerve fascicles in young children with SMA. The counted fascicle numbers of controls in our study were similar to previous descriptions in adults using UHF, histology, or magnetic resonance imaging protocols . Although the mean area of the nerves was about half of that reported in adults, our findings are in line with previous reports of cross‐sectional areas assessed by high‐resolution ultrasonography in children …”
Section: Patients' Characteristics and Ultra–high‐frequency Ultrasounsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with their findings, the present study has demonstrated the feasibility of UHF ultrasound for visualizing single nerve fascicles in young children with SMA. The counted fascicle numbers of controls in our study were similar to previous descriptions in adults using UHF, histology, or magnetic resonance imaging protocols . Although the mean area of the nerves was about half of that reported in adults, our findings are in line with previous reports of cross‐sectional areas assessed by high‐resolution ultrasonography in children …”
Section: Patients' Characteristics and Ultra–high‐frequency Ultrasounsupporting
confidence: 92%
“…Previously, Cartwright et al showed the general feasibility and good interreader reliability of counting fascicles of the median nerve using UHF ultrasound, suggesting the potential of UHF ultrasound as a diagnostic tool or imaging biomarker in several neurological disorders in adults . In agreement with their findings, the present study has demonstrated the feasibility of UHF ultrasound for visualizing single nerve fascicles in young children with SMA.…”
Section: Patients' Characteristics and Ultra–high‐frequency Ultrasounsupporting
confidence: 90%
See 3 more Smart Citations